Away3D 3.6 essentials : take Flash to the next dimension by creating detailer, animated, and interactive 3D worlds with Away3D /: take Flash to the next dimension by creating detailer, animated, and interactive 3D worlds with Away3D. (©2011) - Unknown
No abstract available